Implications between Financial Literacy and Credit Card use among Retirees in Bosnia and Herzegovina (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Financial literacy is crucial in navigating complexities of personal finance, enabling individuals to make informed decisions about budgeting, saving, investing, and borrowing. Financially more literate individuals are better equipped to withstand economic uncertainties, achieve their financial goals, and secure their long-term financial well-being. The aim of this study was to investigate level of financial literacy among retirees in Bosnia and Herzegovina using the “Big Three” financial literacy questions and to connect the results to their credit card usage. Empirical research on 556 respondents showed a very low level of financial literacy/knowledge among retirees as well as a very low rate of adoption and usage of credit cards. Research results point toward need for better financial education of this segment of population in order to raise their financial wellbeing and consequently the life quality as retirees in CEE countries represent a low-income segment of consumers and therefore a financially vulnerable social group that needs better inclusion into society. Furthermore, the research results point toward market opportunities, for financial institutions operating on Bosnian market, to launch a specialized financial product such as credit cards that would be specifically tailored towards the needs of this particular market segment.